Microcomputer programs for chemical engineers / Volume II - Deutsch, David J.; Sanchez, Richard; McGraw-Hill Book Company (New York, NY : McGraw-Hill Book Co., 1987)
Offers more than thirty easy-to-run applications programs designed to help engineers solve problems quickly. Includes documented source codes to permit portability to other systems in conjunction with "C" compiler. The text contains source code listings for all of the programs and may be utilized separately.
A. Engineering mathematics ; Physical properties correlation -- B. Fluid flow ; Heat transfer -- C. Mass transfer ; Engineering economics -- D. Source code programs in C.
Title from disk label.
Text edited by David J. Deutsch and the staff of Chemical engineering, with program translations by Richard Sanchez.
Programs written in C language.
System requirements: IBM PC, XT, AT, or compatible; 128K RAM; PC-DOS or MS-DOS 2.0 or higher; 1-2 disk drives or fixed disk; monochrome or color monitor; printer.
Keywords: Chemical engineering -- Software